Elegia de resurrectione Domini nostri Iesu Christi – Elegia about Resurrection of Our Lord Jesus Christ (edited and translated from Latin by Darius Antanavičius) - Antanavičius, Darius (Senoji Lietuvos literatūra, 2018)
-
Keywords: -